Gendered Habitus and Gender Differences in Academic Achievement - Edgerton, Jason; Peter, Tracey; Roberts, Lance (Alberta Journal of Educational Research, 2014)
Bourdieu’s theory of cultural and social reproduction posits that students’ habitus—learned behavioural and perceptual dispositions rooted in family upbringing—is a formative influence on how they react to their educational environments, affecting academic practices and academic achievement. Although originally conceived as a “class” variant construct, it has been argued subsequently that habitus is also conditioned by gender socialization, and so may also be characterized by significant gender differences. Working with multilevel Canadian data from the linked PISA-YITS surveys, this study investigates gender differences in a Bourdieu derived “structure-disposition-practice” model of academic achievement. For the most part gender differences in the model are modest, but several significant differences are evident: the boys outscore the girls in math and science while the girls excel in reading, students’ socioeconomic stats (SES) has a relatively stronger effect on the girls’ academic achievement than on the boys’ achievement, while students’ habitus affects the boys’ academic achievement more strongly than the girls’ achievement. Finally, the average SES of the schools’ students attend affects both the boys’ and the girls’ academic achievement, but this effect is stronger for the boys, and the effect of the boys’ habitus on their academic achievement diminishes slightly as the average SES of the schools they attend increases; no such contextual interaction was evident for the girls. Overall, the results suggest that habitus and the “structure-disposition-practice” model may still offer a worthwhile contribution to our understanding of gender differences in educational and occupational outcomes, and indeed, merit further empirical investigation. Selon la théorie de Bourdieu sur la reproduction culturelle et sociale, l’habitus des élèves – leurs dispositions comportementales et perceptuelles apprises et ancrées dans leur éducation familiale – constitue une influence formative sur leur réaction à leurs milieux éducationnels, ce qui affecte leur rendement et leurs pratiques académiques. Quoiqu’à l’origine, l’habitus ait été conçu comme un concept qui variait en fonction de la classe sociale, on a établi depuis qu’il est également déterminé par la socialisation liée au sexe et qu’il peut donc se caractérisé par des différences significatives entre les sexes. Puisant dans des données canadiennes à plusieurs niveaux provenant de l’Enquête auprès des jeunes en transition (EJET) et du Programme international pour le suivi des acquis des élèves (PISA), cette étude porte sur les différences entre les sexes dans un modèle de rendement académique « structure-disposition-pratique » dérivé de Bourdieu. De façon générale, les différences entre les sexes sont modestes, mais plusieurs différences significatives se sont toutefois manifestées : le rendement des garçons en mathématiques et en sciences est supérieur à celui des filles; les filles excellent en lecture; le statut socioéconomique (SSE) des élèves a plus d’impact sur le rendement académique des filles que des garçons; et l’habitus des élèves affecte davantage le rendement académique des garçons que celui des filles. Le SSE moyen des élèves de l’école affecte le rendement académique des garçons et des filles, mais l’impact est plus fort chez les garçons. L’effet de l’habitus des garçons sur leur rendement académique diminue un peu avec l’augmentation du SSE moyen des élèves de leur école; cette interaction contextuelle n’a pas été notée chez les filles. Globalement, les résultats portent à croire que l’habitus et le modèle « structure-disposition-pratique » peuvent continuer à enrichir nos connaissances des différences entre les sexes quant au rendement éducatif et professionnel et qu’ils méritent être l’objet de d’autres études empiriques.